The Posterior Parietal Cortex Is Involved in Gait Adaptation: A Bilateral Transcranial Direct Current Stimulation Study - Young, David R.; Parikh, Pranav J.; Layne, Charles S. (Frontiers in Human Neuroscience, 2020)
Gait is one of the fundamental behaviors we use to interact with the world. Functionality of the locomotor system is thus related to enriching interactions with our environment. The posterior parietal cortex (PPC) has been found to contribute to motor adaptation during both visuomotor and postural adaptation tasks. Additionally, structural or functional deficits of the PPC lead to impairments in gait such as shortened steps and increased step width. Based on the aforementioned roles of the PPC, and the importance of gait adaptability, the current investigation sought to identify the role of the PPC in gait adaptation. In order to achieve this, we performed transcranial direct current stimulation (tDCS) over the bilateral PPC prior to performing a split-belt treadmill gait adaptation paradigm. We used three stimulation conditions in a within-subject design. tDCS was administered in a randomized and double-blinded order. Following each stimulation session, subjects first performed baseline walking with both belts running at the same speed. Then, subjects walked for 15 minutes on an uncoupled treadmill, with the belts being driven at a 3:1 speed ratio. Last, they returned to normal (i.e. tied-belt) walking for 5 minutes. Results from 15 young and healthy subjects identified that subjects required more steps to adapt to split-belt walking following suppression of the left hemisphere PPC, contralateral to the fast belt. Furthermore, while suppression of the left hemisphere PPC did not increase the number of steps required to re-adapt to tied-belt walking, this condition did lead to increased magnitude of after-effects. Together, these findings indicate that the PPC is involved in locomotor adaptation. These results support previous literature regarding upper body or postural adaptation and extend these findings to the realm of gait. Results highlight the PPC as a potential target for neurorehabilitation designed to improve gait adaptability.